(untitled) (KULT_online, 2011)
The three dense and concise studies of the publication Russland zwischen Ost und West? Gratwanderungen nationaler Identität (Russia between east and west? Tightrop walks of national identity) dealing with western constructions of Russia as well as with the Russian perception of these heterostereotypes are conceptually united by the theory of "cultural translation". Referring to methods of cultural semiotics, cultural geography and postcolonial theory, the authors examine different aspects of cultural translation from the 18th century until post-Soviet times that overcome the dichotomy between ’East’ and ’West.’ By offering exemplary analyses of discourses and texts such as that on Russian freemasonry, Nikolaj Karamzin and Petr Čaadaev, precursors and spokespeople of Eurasism as well as the writer Boris Akunin, they demonstrate the complexity of Russian identity construction. Well written, this publication can be recommended as introduction to the topic but offers also inspiring thoughts for experts in the field.